PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING (PENGAJARAN TERBALIK) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 4 PEKANBARU - Anggraini, Devi Sri; ', Herdini; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to increase student learning achievement on the topic of hydrocarbons inclass X Senior High School (SMAN) 4 Pekanbaru. The research is a kind of experiment research with pretest-posttest design. The sample was determined after doing normality and homogeneity test of 9 classes as population and then class X9 as experiment class and X7 as control class. Experimental class is a class that is applied to Reciprocal Teaching models while the control class was not. Data analysis technique used is the t-test and N-gain normalized test. Based on data analysis of data obtained tcount> ttable is 4.93>1.67, means that the application of Reciprocal Teaching models can improve student learning achievement on the topic of hydrocarbons in class X Senior High School (SMAN) 4 Pekanbaru. The category improvement of student achievement at experiment class was high category with N-gain normalized is 0,83. Meanwhile, the category improvement of student achievement in control class was medium category with N-gain normalized is 0,68.Keywords : Achievement, Reciprocal Teaching, Hydrocarbons